The Ark of Nuh - Khan,saniyasnain (china goodwordbooks, 2020)
"The Ark of Nuh" by Saniyasnain Khan is a children's book that retells the story of Prophet Noah (Nuh) and the Great Flood from the Quran. The book, often part of the "Quran Stories for Little Hearts" series, focuses on how Allah saved Prophet Nuh, the believers, and pairs of all animals from the devastating flood by instructing them to build the Ark. The story emphasizes Allah's kindness to believers and his wrath towards those who reject his message.